Financial reporting in times of uncertainty : Covid-19 pandemic impact on financial statements in Finland - Saarikoski, Alina (My University, 2021)
Abstract In March 2020 World Health Organization declared a Covid-19 pandemic. During the following weeks, governments of European countries set restrictive measures to control the spread of the virus. The set measures have changed consumer behavior and treated industries differently. Industries, such as tourism and restaurant have suffered severely since the restrictions impact directly on their core businesses. While companies operating in retail and providing streaming services have benefited from increased sales caused by the pandemic. The aim of this thesis is to study how the Covid-19 pandemic, and uncertainty resulting from the pandemic, impact Finnish listed companies’ financial reporting. In the study, the focus is on how the companies have applied IAS 1 – Presentation of Financial Statements standard due to the Covid-19 pandemic. IFRS Foundation, authorities, and big-4 accounting firms have provided instructions on how companies should apply IFRS standards during the Covid-19 pandemic. Because of the high uncertainty and low predictability, companies shall carefully assess how the Covid-19 impacts the company, its future, and recognized amounts. In this research, year 2020 financial reports of six Finnish companies are analyzed. Especially, the application of IAS 1 standard is under evaluation. The selected companies represent different industries. Each of the companies’ profitability has either increased or decreased due to the pandemic. The research shows the companies whose profitability the Covid-19 pandemic has impacted negatively have discussed the pandemic impact in detailed level and extensively in their financial statements. External stakeholders find these kinds of disclosures helpful since it decreases the level of information asymmetry. While the companies whose profitability had improved due to the pandemic had discussed the Covid-19 impact on a general level, which is not found helpful from external stakeholders’ point of view. There is only a limited number of accounting studies considering the Covid-19 since the pandemic is still ongoing. However, differences between the companies could be explained by accounting conservatism, attributional biases, and inflexibility of financial report preparation processes.

Maaliskuussa 2020 Maailman terveysjärjestö julisti koronaviruksen pandemiaksi. Seuraavien viikkojen aikana Euroopan maiden hallitukset asettivat rajoituksia hidastaakseen viruksen leviämistä. Asetetut rajoitukset ovat muuttaneet kuluttajakäyttäytymistä ja kohdelleet toimialoja eri tavoin. Toimialat, kuten turismi ja ravintola-ala, ovat kärsineet vakavasti, koska asetetut rajoitukset kohdistuvat niiden ydinliiketoimintaan. Vähittäiskauppa- ja suoratoistopalveluita tarjoavat yritykset taas ovat hyötyneet pandemian myötä kasvaneesta kysynnästä. Tämän tutkielman tarkoituksena on selvittää miten Covid-19 pandemia, ja siitä johtuva liiketoimintaympäristön epävarmuus, vaikuttavat suomalaisten pörssiyhtiöiden tilinpäätösraportointiin. Tutkimuksessa keskitytään tarkastelemaan sitä, miten yhtiöt ovat soveltaneet koronaviruspandemian vuoksi tilinpäätösten esittämistä säätelevää IAS 1 -standardia. IFRS-säätiö, viranomaiset ja Big4-tilintarkastusyhteisöt ovat ohjeistaneet yhtiötä siitä, miten IFRS-standardeja tulisi soveltaa Covid-19 pandemian aikana. Epävarmuuden ja heikon ennustettavuuden johdosta yhtiöiden tulisi kiinnittää erityistä huomiota siihen, miten Covid-19 on vaikuttanut yhtiöön, tulevaisuuteen ja raportoituihin lukuihin. Tutkimuksessa analysoidaan kuuden suomalaisen pörssiyhtiön tilinpäätöksiä vuodelta 2020. Tarkastelun kohteena on IAS 1 -standardin soveltaminen. Valitut yhtiöt edustavat eri toimialoja. Jokaisen yhtiön kannattavuus on joko parantunut tai heikentynyt koronaviruspandemian vuoksi. Tutkimus esittää, että yhtiöt, joiden kannattavuuteen Covid-19 on vaikuttanut negatiivisesti, ovat keskustelleet pandemian vaikutuksista yksityiskohtaisesti ja laajasti tilinpäätöksissä. Tämänkaltainen raportointi on ulkoisten sidosryhmien näkökulmasta hyödyllistä, koska se vähentää informaatio asymmetriaa. Kun taas yhtiöt, joiden kannattavuus on parantunut, ovat keskustelleet pandemian vaikutuksista yleisemmällä tasolla, mikä ei ole ulkoisten sidosryhmien näkökulmasta yhtä hyödyllistä. Covid-19 pandemian vaikutuksia kirjanpitokäytäntöihin ja tilinpäätöksiin on tutkittu vähän, koska pandemia on edelleen käynnissä. Yhtiöiden raportointikäytäntöjen välillä havaittuja eroja voidaan kuitenkin osittain selittää kirjanpidon konservatismilla, attribuutioharhoilla ja tilinpäätöksien valmisteluprosessien joustamattomuudella.
Keywords: Covid-19, IAS 1, uncertainty, financial reporting, accounting conservatism